PENGARUH PERSIA, TURKI, DAN BYZANTIUM DALAM PERADABAN BANI ABBASIYAH - Muhammad Amin (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
The Golden Era of Islam was gained in Abbasid dynasty. In this Era, Muslims reached the highest glory and civilization, especially in education and infrastructure. However, the educational progress was not accompanied by stability of political and economical conditions. During the five centuries of Abbasid rule, the dynasty was only able to rule independently in the last periode but their power is concentrated in the city of Baghdad. Abbasid dynasty was ruled by the Persian and Turks, so there are a wide variety of civilization during the Abbasid period was affected by the Persian-Turkish culture. Bilateral relation between the Abbasids and Byzantine empire also influenced the development of Islamic civilization because the massive translation of Greek works were stored in a warehouse the Byzantine empire especially in al-Makmun era.